2019
DOI: 10.1590/1678-5150-pvb-6200
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and minimal inhibitory concentration of bacteria isolated from the eyes of dogs with keratoconjunctivitis sicca

Abstract: The objective of this study was to evaluate the antimicrobial susceptibility profile of bacteria isolated from the eyes of dogs with keratoconjunctivitis sicca (KCS). We evaluated 65 dogs diagnosed with KCS and 30 healthy dogs (Control Group). Conjunctival swab samples were collected after KCS was diagnosed. Microbiological examinations were performed, including aerobic culture, antimicrobial susceptibility testing and minimum inhibitory concentration (MIC) determination for chloramphenicol, tobramycin, ofloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, few studies considered its different degrees for evaluations (Balicki The variation in the clinical presentation of KCS in specific dog breeds has been little explored (Herrera et al 2007, Sanchez et al 2007, Kitamura et al 2019). The Shih Tzu breed was described as predisposed to the development of quantitative KCS (Kaswan & Salisbury 1990, Sanchez et al 2007, Giuliano 2013, Arnold et al 2014, Oliveira et al 2014, Pereira et al 2019a) and identified as one of the breeds most affected by the disease in surveys carried out in the United States (Kaswan & Salisbury 1990), United Kingdom (Sanchez et al 2007), Taiwan (Liu et al 2014), andBrazil (Oliveira et al 2014). However, ophthalmologic evaluations between the different degrees of KCS in Shih Tzu dogs have not been found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies considered its different degrees for evaluations (Balicki The variation in the clinical presentation of KCS in specific dog breeds has been little explored (Herrera et al 2007, Sanchez et al 2007, Kitamura et al 2019). The Shih Tzu breed was described as predisposed to the development of quantitative KCS (Kaswan & Salisbury 1990, Sanchez et al 2007, Giuliano 2013, Arnold et al 2014, Oliveira et al 2014, Pereira et al 2019a) and identified as one of the breeds most affected by the disease in surveys carried out in the United States (Kaswan & Salisbury 1990), United Kingdom (Sanchez et al 2007), Taiwan (Liu et al 2014), andBrazil (Oliveira et al 2014). However, ophthalmologic evaluations between the different degrees of KCS in Shih Tzu dogs have not been found.…”
Section: Discussionmentioning
confidence: 99%
“…Cytohistomorphological analyses of the ocular surface of KCS carrier animals demonstrate conjunctival inflammatory infiltrate, reduced goblet cell density, and squamous metaplasia (Marek & Podhorska 1995, Balicki et al 2011, Radziejewski et al 2018. Moreover, studies that evaluated the ocular microbiota of dogs of different breeds with the disease indicate a higher contamination rate and opportunistic bacteria (Oria et al 2013, Pereira et al 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…The disk diffusion test was performed according to Pereira, et al [50], Andrews [51], Mostafa, et al [52], with some modifications. Rosemary extracts filtered with a sterilized Millipore filter (0.22 µm) at a volume of 50 mg/mL and were added to a sterilized filter paper disk (8 mm in diameter).…”
Section: Microbiological Activity 451 Disk Diffusion Screeningmentioning
confidence: 99%
“…The disc diffusion test was performed according to Andrews (2001), Mostafa, Al-Askar et al (2018), and Pereira, Zulim et al (2019 with some modifications. Rosemary extracts at 50 mg/mL were filtered with a sterilized Millipore filter (0.22 µm) and added to a sterilized filter paper disc (8mm of diameter).…”
Section: Diffusion Discsscreeningmentioning
confidence: 99%